2019
DOI: 10.1093/jac/dkz460
|View full text |Cite
|
Sign up to set email alerts
|

Duration of pretomanid/moxifloxacin/pyrazinamide therapy compared with standard therapy based on time-to-extinction mathematics

Abstract: Objectives Animal models have suggested that the combination of pretomanid with pyrazinamide and moxifloxacin (PaMZ) may shorten TB therapy duration to 3–4 months. Here, we tested that in the hollow-fibre system model of TB (HFS-TB). Methods A series of HFS-TB experiments were performed to compare the kill rates of the PaMZ regimen with the standard three-drug combination therapy. HFS-TB experiments were performed with bacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…Given this mathematical property, we could use morphisms to calculate a multistep transformation function to map the time to extinction from the HFS-TB to patients. In TB, this approach correctly predicted cure rates versus duration of therapy in several clinical trials of novel TB regimens ( 11 , 16 ). Here, we used the same ordinary differential equations and category theory with serial sputum M. kansasii TTP in a cohort of Taiwanese patients with pulmonary disease on treatment with IDSA recommended therapy and from HFS of pulmonary M. kansasii (HFS- Mkn ) on standard therapy ( 17 , 18 ).…”
Section: Textmentioning
confidence: 99%
“…Given this mathematical property, we could use morphisms to calculate a multistep transformation function to map the time to extinction from the HFS-TB to patients. In TB, this approach correctly predicted cure rates versus duration of therapy in several clinical trials of novel TB regimens ( 11 , 16 ). Here, we used the same ordinary differential equations and category theory with serial sputum M. kansasii TTP in a cohort of Taiwanese patients with pulmonary disease on treatment with IDSA recommended therapy and from HFS of pulmonary M. kansasii (HFS- Mkn ) on standard therapy ( 17 , 18 ).…”
Section: Textmentioning
confidence: 99%
“…The HFIM’s strength is in testing the effects of combination therapy as it can mimic human PK profiles of different drugs accurately. HFIM experiments on the PaMZ drug regimen in the STAND trial [ 8 ] revealed that the time-to-sterilisation for the above was identical to that of standard therapy, thereby indicating that the regimen being investigated would likely not shorten treatment duration [ 64 ]. HFIM experiments in combination with modelling tools can be used to predict the duration of treatment required for a particular combination therapy.…”
Section: Application Of Hfim In Evaluating Combination Therapymentioning
confidence: 99%
“…HFIM experiments in combination with modelling tools can be used to predict the duration of treatment required for a particular combination therapy. Srivastava et al hypothesise that to shorten treatment time to 2 months, the trajectory of bacterial sterilisation would need to be three times steeper than that of standard therapy [ 64 ]. This could serve as a guide for future trials investigating the potential of drug combinations in reduction in treatment time.…”
Section: Application Of Hfim In Evaluating Combination Therapymentioning
confidence: 99%
“…A mechanism-based PK-PD model by Hollow-fiber systems for TB has the advantage of being able to mimic dynamic PK in comparison to more traditional static time-kill experiments. A semi-mechanistic PK-PD model can be derived using HTS data [117][118][119]. Khan et al describes susceptible, resting, and non-colony-forming bacterial populations [120].…”
Section: Prediction Of Human Pharmacokinetic-pharmacodynamic Relationmentioning
confidence: 99%